The Nature of an English Test: Difficulty Index and Distractor Analysis - Rusma Setiyana; Endah Anisa Rahma; Rina Syafitri (Universitas Teuku Umar, 2020)
Language assessment plays such a vital role in English teaching and learning process to measure students’ ability. Doing mistake in creating test items leads the failure in finding out presumption of the student’s achievement. This research was expected to break down the nature of English test including the difficulty index and the adequacy of distractors as a part of an english language assessment. Content analysis was utilized in this study by using two different techniques, namely check list and document analysis to collect the information data. The information from checklist were investigated by utilizing a factual method in percentage and the information from archive examination were analyzed by using a test item analysis software. The result demonstrates that in the term of difficulty index, the english item test met 48% to be acknowledment and the presentage of distractor effectiveness of English test was 41%. It means that more than 50% of the test should be revised and removed.